Representasi Standar Kecantikan Korea Citra Modern dalam Iklan Somethinc oleh Han So Hee - Fajar Junaedi; Nasywa Haura Fathiyya Hafizhah (Universitas Muhammadiyah Klaten, 2026)
The development of digital technology has driven the transformation of advertising practices, particularly in the beauty industry, which increasingly utilizes digital media platforms such as YouTube. This study aims to analyze how Somethinc advertisements represent Korean culture and K-beauty standards in their content. This study uses a descriptive qualitative approach with Roland Barthes' semiotic analysis method, which examines meaning at two levels of significance, namely denotation and connotation, as well as the myths constructed through advertising. The object of this study is a Somethinc advertisement titled “Look And Be Your Own Girl Crush With Somethinc” uploaded on the YouTube platform. Data collection techniques were carried out through indirect observation, documentation, and literature study, with data validation using source and theory triangulation. The results of the study show that Somethinc advertisements denotatively display women with fair, smooth skin and confident expressions in their daily self-care activities. At a connotative level, the advertisement constructs a meaning of ideal beauty that refers to K-beauty standards, such as fair, clear, and glowing skin, which are then mythologized as symbols of a modern and feminine lifestyle. This representation shows how Korean culture is adapted by local Indonesian brands to increase the appeal of their products, while also potentially shaping consumer perceptions and preferences towards certain beauty standards.